A 2000 year natural record of magnitudes and frequencies for the largest Upper Colorado River floods near Moab, Utah. Issue 6 (30th June 2014) - Greenbaum, Noam; Harden, Tessa M.; Baker, Victor R.; Weisheit, John; Cline, Michael L.; Porat, Naomi; Halevi, Rafi; Dohrenwend, John
Abstract Using well‐established procedures for paleoflood hydrology and employing optically stimulated luminescence (OSL) geochronology, we analyzed a very well‐preserved natural record of 44 Upper Colorado River extreme floods with discharges ranging from 1800 to 9200 m3s−1. These are the largest floods occurring during the last 2140 ± 220 years, and this natural record indicates that large floods are much more frequent than can be estimated by extrapolation from the stream gaging record that extends back to 1914. Most of these large floods occurred during the last 500 years, and the two largest floods in the record both exceeded the probable maximum flood (PMF) estimated at 8500 m3s−1 (300, 000 cfs) for nearby Moab, Utah. Another four floods, with discharges greater than 7000 m3s−1, occurred during the last two millennia. Flood frequency analyses using the FLDFRQ3 model yields the following values, depending on the Manning n roughness coefficients: 100 yr flood—4670–4990 m3s−1; 500 yr flood—6675–7270 m3s−1; 1000 yr flood—7680–8440 m3s−1. The presumed PMF discharge (8500 m3s−1) gets assigned a recurrence interval of about 1000 years, and the largest historical 1884 flood (3540 m3s−1)—a recurrence interval of <100 years. Flood frequency analysis for the Moab Valley based on the gaged record (1914–2012) yield 2730 m3s−1 for the 100 yr flood and 3185 m3s−1 for the 500 yr flood. This underestimation of the frequency of large floods from the gage data results from effects on that record by modern regulation of upstream river flow and associated water extraction for agriculture.